An unusual presentation of extra-hepatic portal venous obstruction - Krishna, Vidya; Ramanan, Padmasani Venkat; Sankaranarayan, Shuba; Prabaharan, Krithika (Indian Journal of Child Health, 2015)
A 13-year-old girl presented with short duration of fever, left upper abdominal pain and massive tender splenomegaly. There was no evidence of liver dysfunction or significant history. Evaluation revealed multiple splenic infarcts with portal vein thrombosis. She developed splenic abscess and was managed conservatively with percutaneous drainage and antibiotics.